Caracterização molecular de acessos de mandioca de mesa coletados nas regiões urbanas de Maringá e de Toledo - Silva, Luciano Ivano da (2010)
This study aimed to characterize 137 sweet cassava accessions from urban regions of Maringá and Toledo in Paraná state, using RAPD molecular markers. The use of 15 decamer primers in Maringá population resulted in a total of 100 amplified bands, considering that 89 of them were polymorphic with size ranging from 200 to 2,000 pb. On the other hand, in the population from Toledo it was observed a total of 102 amplified bands, from which 94 were polymorphic with size varying from 200 to 1,800 pb. The data was submitted to statistical analyses. Genetic variability was analyzed through matrix construction (binary data) by quantifying genetic variability inter- and intra-geographic groups, verified by molecular variance analysis (AMOVA) and also by clustering analysis (UPGMA). The most divergent combinations from Maringá accessions were BGM 20 and BGM 232 (dii' = 0.607), BGM 20 and BGM 179 (dii' = 0.591), BGM 20 and BGM 326 (dii' = 0.591), while the most similar ones were BGM 105 and BGM 119 (dii' = 0.083), BGM 34 and BGM 37 (dii' = 0.105). In addition, the most divergent combinations from Toledo accessions were BGM 450 and BGM 487 (dii' = 0.736), BGM 463 and BGM 495 (dii' = 0.719), BGM 463 and BGM 484 (dii' = 0.718), BGM 452 and BGM 463 (dii' = 0.717). In Toledo, the lowest genetic divergence were observed in the following pairs: BGM 484 and BGM 485 (dii'= 0.153), BGM 432 and BGM 468 (dii' = 0.186). The UPGMA clustering method revealed the formation of 11 and 16 groups in the cities of Toledo and Maringá, respectively. Variability quantification inter- and intra-geographic groups, verified by AMOVA, were respectively estimated in 26.24% and 73.75%, indicating high variability inter-geographic groups. However, the highest intra-groups variance was noted among accessions from Toledo group, since it was verified higher similarity among accessions from Maringá group, considering the most divergent combinations were revealed by the combination of the accessions BGM 451 x BGM 88, followed by BGM 451 x BGM 162. The results have evidenced the existence of ample genetic divergence between sweet cassava accessions collected from Maringá and Toledo.